6y-2(y-2)+5=

Simple and best practice solution for 6y-2(y-2)+5= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6y-2(y-2)+5= equation:


6y-2(y-2)+5=0

We simplify the equation to the form, which is simple to understand
6y-2(y-2)+5=0

Reorder the terms in parentheses
6y+(-2y+4)+5=0

Remove unnecessary parentheses
+6y-2y+4+5=0

We move all terms containing y to the left and all other terms to the right.
+6y-2y=0-4-5

We simplify left and right side of the equation.
+4y=-9

We divide both sides of the equation by 4 to get y.
y=-2.25

See similar equations:

| 5e+12= | | 4x-4b+x^2b-x^3=0 | | (x+3)=(3x-91) | | (2x+1)=(3x-4) | | ax-bx-a^2+b^2=2a-2b | | ax-bx-a^2+b^2=2ab-2b | | (2x+15)=(6x-57) | | x^7=16870 | | x-2=.5x+5 | | 9y^3-7=y-63y^2 | | .75x-.25x+5=27 | | x-4=25/5 | | 4+5x=-4(-7x-1) | | 4q+1-5q-1= | | 4x^2-1=10x | | z+1=.5z+4 | | 7x-21y=10x+-45y | | 2(-4-x)= | | 12x^2-13x-1=0 | | -4(2+x)= | | xxx=9 | | 2(-4+x)= | | 12x^2-13x=1 | | 5(3a-6)5a=-12+a | | 5n^2+75n=3500 | | 5+29t-16t^2=12 | | 2s(8s+7)-4s=3(4s+1)-5 | | (x+1)(x+7)(2x-1)=0 | | 4y+81=81 | | 4m^2-2m-5=0 | | x^2-x+1.25=0 | | 7+4n-2=8n+8-3n |

Equations solver categories